2018
DOI: 10.1016/j.mayocpiqo.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Joint Corticosteroid Injection Associated With Increased Influenza Risk

Abstract: Aging and immunocompromising conditions or medications may reduce influenza vaccine effectiveness. The high-dose vaccine has been used to improve vaccine response in patients 65 years and older. Because of systemic immunosuppressive effects, oral corticosteroids may reduce vaccine effectiveness; however, despite over half a century of use, no data are available regarding the effect of joint and bursa corticosteroid injection on influenza vaccine effectiveness. The aim of this retrospective study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 3 publications
0
54
1
4
Order By: Relevance
“…Early evidence of the potential effect of single-dose corticosteroid exposure is described in a report on an observational cohort from the Mayo Clinic. This study investigated the association of a single intra-articular corticosteroid injection with increased risk of influenza infection [ 18 ]. Over a period of five influenza seasons, the rate of influenza infection was compared in vaccinated patients who had received an intra-articular corticosteroid injection vs those who had not.…”
Section: Systemic Corticosteroid Increases Infection Riskmentioning
confidence: 99%
“…Early evidence of the potential effect of single-dose corticosteroid exposure is described in a report on an observational cohort from the Mayo Clinic. This study investigated the association of a single intra-articular corticosteroid injection with increased risk of influenza infection [ 18 ]. Over a period of five influenza seasons, the rate of influenza infection was compared in vaccinated patients who had received an intra-articular corticosteroid injection vs those who had not.…”
Section: Systemic Corticosteroid Increases Infection Riskmentioning
confidence: 99%
“…Evidence for the effects of corticosteroid (CS) injection on risk of viral infection is even more limited. A large retrospective study from 2018 reported an increased risk of influenza among flu-vaccinated patients who had a CS injection compared with those without [4]. The authors reported a single unadjusted relative risk (RR) corresponding to a 52% higher risk of influenza associated with CS injections.…”
Section: Dear Editormentioning
confidence: 99%
“…However, no literature exists specifically examining whether steroid injections potentiate the risk of contracting COVID‐19. Several studies have found increased risk for immunosuppression 38 and contraction of influenza 39 . If use of steroid is deemed necessary, consider reducing the steroid dose or using dexamethasone or betamethasone as the duration of immune suppression is less 40 .…”
Section: Specific Risk Mitigation For Pain Proceduresmentioning
confidence: 99%